(untitled) (Brazilian Journal of Radiation Sciences (BJRS), 2024)
Techniques based on neutron beams are used in research, industry and medicine being especially suitable for the characterization of a wide variety of materials. Neutron radiation can be produced using nuclear reactors, isotopic sources, or particle accelerators. Since the number of reactors is in decline and isotopic sources are expensive and difficult to handle, neutron generator (NG) technology has experienced significant development. Neutron generators are safer than nuclear reactors and isotopic sources, and the use of NGs is increasing worldwide, including in Brazil. This article reviews the main applications of neutron radiation, neutron production techniques, and specifically the technologies used in neutron generators. An overview of the utilization of these techniques in Brazil is presented, along with studies on acquisition and start-up costs of neutron-generating equipment and perspectives for future utilization in various areas.